Challenges for the Therapeutic use of Pluripotent Stem Derived Cells - Forsberg, Magda; Hovatta, Outi (Frontiers in Physiology, 2012)
Human embryonic stem cells (hESC) and induced pluripotent stem cells (hiPSC) are an attractive cell source for regenerative medicine. These cells can be expanded to vast numbers and can be differentiated to many cell types to generate pluripotent stem cells (PSC) derived therapeutic cells. These cells are desired for cell transplantations. Cell replacement is promising, but it has many challenges. The challenge of introduction of exogenous cells in a recipient requires addressing several different topics; the immunological response and possible rejection, cleanliness, exclusion of tumor formation and functionality of the PSC derived therapeutic cells. Immunological rejection can be addressed with immunomodulation of the cells and the recipient. Cleanliness can be optimized using good manufacturing practice (GMP) quality systems. Tumor formation requires the removal of any PSC remaining after differentiation. At last, the functionality of the cells must be tested in in-vitro and in animal models. After addressing these challenges, precise strategies are developed to monitor the status of the cells at different times and in case of undesired results, corresponding counteracting strategies must exist before any clinical attempt.